Compositions for vibration-damping rubber and vibration-damping rubber

JP2026167130APending Publication Date: 2026-10-14SUMITOMO RIKO CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025060526
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0015】 本開示の防振ゴム用組成物および防振ゴムによると、耐久性と高減衰性との両方を実現することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026167130000001
    Figure 2026167130000001
  • Figure 2026167130000002
    Figure 2026167130000002
Patent Text Reader

Abstract

The present invention provides vibration-damping rubber that satisfies desired durability and damping properties, and a composition for vibration-damping rubber that is the material for such rubber. [Solution] The vibration-damping rubber composition comprises a diene rubber and multilayer particles having a first layer forming the outermost layer of the particles and a second layer disposed inside the first layer. The first layer of the multilayer particles is made of a polymer formed by polymerizing vinyl monomers containing monomers having vulcanization-reactive functional groups, and the second layer consists of one or more layers and is made of a polymer formed by polymerizing one or more monomers containing acrylic acid esters. The vibration-damping rubber is made of the vulcanized product of the vibration-damping rubber composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to vibration-damping rubber used in vehicles and the like, and a composition for vibration-damping rubber that is a material thereof.

Background Art

[0002] In vehicles such as automobiles, vibration-damping members are arranged at sites that are sources of vibration and noise, to reduce vibration transmission and noise diffusion. As vibration-damping members, those provided with vibration-damping rubber are known, and the vibration-damping rubber is required to have strength for supporting heavy objects such as engines, and damping properties for mitigating or absorbing the transmission of vibration energy. For example, butyl rubber is excellent in damping properties. Therefore, it is used as a material for vibration-damping rubber alone or by blending with other rubbers. Patent Document 1 describes a vibration-damping rubber using a blend material of natural rubber and butyl rubber as a rubber component. Patent Document 2 describes a vibration-damping rubber with a sea-island structure in which butadiene rubber is dispersed in a matrix of chlorinated butyl rubber.

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Patent Document 2

Patent Document 3

Summary of Invention

Problems to be Solved by the Invention

[0004] However, while butyl rubber has the advantage of excellent damping properties, its durability is insufficient. As described in Patent Documents 1 and 2 above, even when butyl rubber is blended with other rubbers, the bonding between the rubber components is insufficient, making it easy to delaminate at the interface and difficult to improve durability. In particular, in the case of a sea-island structure as described in Patent Document 2, the size and dispersion state of the island phases are easily changed depending on the mixing conditions, and there is a problem in that it is difficult to control the phase separation structure which greatly affects the physical properties. Thus, simply combining butyl rubber, which has excellent damping properties, with other rubbers makes it difficult to realize vibration-damping rubber that satisfies both durability and damping properties.

[0005] This disclosure has been made in view of the above circumstances, and aims to provide vibration-damping rubber that satisfies desired durability and damping properties, and a vibration-damping rubber composition which is a material for the same. [Means for solving the problem]

[0006] (1) In order to solve the above problems, the vibration-damping rubber composition of the present disclosure comprises a diene rubber and a multilayer particle having a first layer forming the outermost layer of the particle and a second layer disposed inside the first layer, wherein the first layer is made of a polymer obtained by polymerizing vinyl monomers containing a monomer having a vulcanization-reactive functional group, and the second layer consists of one or more layers and is made of a polymer obtained by polymerizing one or more monomers containing an acrylic acid ester.

[0007] The vibration-damping rubber composition disclosed herein comprises a diene rubber and multilayer particles composed of a predetermined polymer. The outermost layer of the multilayer particles, the first layer, consists of a polymer of vinyl monomers containing a monomer having a vulcanization-reactive functional group. This polymer crosslinks with the diene rubber via the vulcanization-reactive functional group. This makes it less likely for delamination to occur at the interface between the multilayer particles and the rubber matrix, and the durability of the vulcanized product obtained by vulcanizing the vibration-damping rubber composition is less likely to decrease. The second layer, located inside the first layer, consists of a polymer of one or more monomers containing an acrylic acid ester. The inclusion of an acrylic acid ester makes the damping properties of the polymer relatively high. In this way, by adding multilayer particles, in which the first layer mainly exhibits a durability-improving effect and the second layer mainly exhibits a damping-improving effect, to the diene rubber, both durability and high damping properties are achieved in the vulcanized product. Furthermore, the multilayer particles can maintain their shape without melting even when mixed with materials such as diene rubber during the process of manufacturing vibration-damping rubber. Therefore, by adjusting the particle size of the multilayer structure particles, it is easier to achieve a dispersion form that produces the desired effect.

[0008] Incidentally, Patent Document 3 describes a tire rubber composition containing multilayer polymer particles. However, this composition is for manufacturing tires, not vibration-damping rubber. Therefore, in this composition, the components of the polymer (X) layer and polymer (Y) layer constituting the multilayer polymer particles are adjusted to achieve the wet grip required for tires and a balance between wet grip and wear resistance. In this respect, it differs from the vibration-damping rubber composition disclosed in this disclosure, which aims for durability and damping. Furthermore, in recent years, it has become necessary to reduce vibrations in the high-frequency range (e.g., 1000 to 10000 Hz) generated by electric motors in order to accommodate not only gasoline-powered vehicles but also electric vehicles powered by electric motors. For this reason, it is desirable for vibration-damping rubber to exhibit high damping performance in a wide frequency range including the high-frequency range, but damping performance has not been considered in Patent Document 3.

[0009] (2) In the above configuration, the monomer having the vulcanization-reactive functional group in the first layer may be one or more selected from allyl methacrylate, diallyl phthalate, triallyl isocyanurate, 1,2-butadiene, and 1,3-butadiene. With this configuration, vulcanization-reactive functional groups such as carbon-carbon double bonds, allyl groups, and vinyl groups can be easily introduced into the polymer of the first layer.

[0010] (3) In any of the above configurations, the polymer forming the second layer may be crosslinked. With this configuration, even when mixed with materials such as diene rubber during the process of manufacturing the vibration-damping rubber, the shape of the multilayer structure particles can be maintained and the particle size is less likely to change. This makes it easier to achieve a dispersion form that provides the desired effect.

[0011] (4) In any of the above configurations, the glass transition temperature of the second layer may be set to be between -60°C and 40°C. In polymer materials, damping tends to occur around the glass transition temperature (Tg). According to the vibration-damping rubber composition of this disclosure, damping can be expressed in any temperature range by adjusting the Tg of the second layer in the multilayer particle structure. As an indicator of Tg, the peak temperature of the loss coefficient (tanδ) obtained by measuring dynamic viscoelasticity is used. For example, a large tanδ in the low-temperature region indicates high damping in the high-frequency region. With this configuration, since the lower limit of the Tg of the second layer is a low temperature of -60°C, damping can be expressed in a higher frequency region.

[0012] (5) In any of the above configurations, the mass ratio of the first layer in the multilayer structure particles may be 5% by mass or more and 50% by mass or less when the total mass of the multilayer structure particles is 100% by mass. For example, if the Tg of the second layer is low and the second layer is relatively soft, and the mass ratio of the first layer is too small, in other words, if the first layer is too thin, the multilayer structure particles may stick together and the dispersibility may decrease. Conversely, if the mass ratio of the first layer is too large, in other words, if the first layer is too thick, the damping improvement effect of the second layer will not be easily achieved. This configuration is suitable from the viewpoint of the dispersibility of the multilayer structure particles, the durability of the vulcanized product and the damping properties.

[0013] (6) In any of the above configurations, the content of the multilayer structure particles may be 5 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the diene rubber. This configuration makes it possible to achieve a good balance between the durability and damping properties of the vulcanized product.

[0014] (7) The vibration-damping rubber of this disclosure consists of a vulcanized product of a vibration-damping rubber composition having any of the above configurations. As described above, the first layer, which forms the outermost layer of the multilayer structure particles, is crosslinked with the diene rubber by vulcanization-reactive functional groups. As a result, the vibration-damping rubber of this disclosure maintains durability even when it contains multilayer structure particles. In addition, high damping performance is achieved due to the damping improvement effect of the second layer of the multilayer structure particles. [Effects of the Invention]

[0015] The vibration-damping rubber composition and vibration-damping rubber of this disclosure can achieve both durability and high damping properties. [Modes for carrying out the invention]

[0016] The embodiments of the vibration-damping rubber composition and vibration-damping rubber described herein will be explained below. However, the embodiments are not limited to those described below, and can be implemented in various modified and improved forms as possible for those skilled in the art. Numerical ranges indicated using "~" in this specification include the values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described stepwise in this specification, the individually stated upper and lower limits can be combined in any way. Furthermore, the upper and lower limits of the numerical ranges can be replaced with the values ​​shown in the examples.

[0017] <Composition for vibration-damping rubber> The vibration-damping rubber composition of this disclosure comprises a diene rubber and multilayer particles.

[0018] [Diene-based rubber] Examples of diene rubbers include natural rubber (NR), butadiene rubber (BR), styrene-butadiene rubber (SBR), chloroprene rubber (CR), isoprene rubber (IR), acrylonitrile-butadiene rubber (NBR), ethylene-propylene-diene rubber (EPDM), butyl rubber (IIR), and chloroprene rubber (CR). One or more of these can be used in combination. Among these, natural rubber is preferred from the viewpoint of strength.

[0019] [Multilayer structured particles] A multilayer particle has a first layer that forms the outermost layer of the particle, and a second layer that is located inside the first layer.

[0020] (1) First layer The first layer consists of a polymer obtained by polymerizing vinyl-based monomers including a monomer having a vulcanization-reactive functional group. In the present specification, "polymer" includes both "homopolymer" and "copolymer". The vinyl-based monomers may be composed only of the monomer having a vulcanization-reactive functional group, or may be composed of both the monomer having a vulcanization-reactive functional group and a monomer having no vulcanization-reactive functional group. Since the polymer of the first layer comprises structural units formed by polymerizing the monomer having a vulcanization-reactive functional group, it bonds with the rubber component during the vulcanization reaction of the diene rubber, and mainly contributes to improving the durability of the vulcanizate. The content of the monomer having a vulcanization-reactive functional group in the composition for forming the polymer of the first layer is desirably 30 to 100 mass% when the total amount of the composition is taken as 100 mass%. It is more preferably 40 mass% or more.

[0021] The vulcanization-reactive functional groups include carbon-carbon double bonds, allyl groups, vinyl groups and the like. In consideration of the affinity and dispersibility for diene rubber, the monomer having a vulcanization-reactive functional group is desirably one or more selected from allyl methacrylate, diallyl phthalate, triallyl isocyanurate, 1,2-butadiene, and 1,3-butadiene.

[0022] The mass proportion of the first layer in the multilayer-structured particle is not particularly limited, but in consideration of the dispersibility of the multilayer-structured particle, the durability improving effect by the first layer, and the like, it is desirably 5 mass% or more when the total amount of the multilayer-structured particle is taken as 100 mass%. It is more preferably 10 mass% or more, and further 15 mass% or more. On the other hand, in consideration of the damping performance improving effect by the second layer, the mass proportion of the first layer is desirably 50 mass% or less when the total amount of the multilayer-structured particle is taken as 100 mass%. It is more preferably 40 mass% or less, and further 30 mass% or less.

[0023] (2) Second layer The second layer consists of a polymer formed by the polymerization of one or more monomers, including an acrylic acid ester. The second layer may be a single layer or multiple layers of two or more. The monomers used in the second layer may consist solely of acrylic acid esters, or it may consist of both acrylic acid esters and other monomers. For example, a form using acrylic acid esters and methacrylic acid esters is preferred. Acrylic acid esters have relatively high durability and excellent damping properties. Since the polymer of the second layer contains constituent units polymerized from acrylic acid esters, it mainly contributes to improving the damping properties of the vulcanized product. Furthermore, when mixed with materials such as diene rubber, it is desirable that the polymer of the second layer be crosslinked in order to maintain the shape of the multilayer structure particles, suppress changes in particle size, and easily achieve the desired dispersion state.

[0024] Examples of acrylic acid esters include alkyl acrylates such as methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, octyl acrylate, dodecyl acrylate, stearyl acrylate, and behenyl acrylate, as well as aromatic ring-containing acrylic acid esters such as phenoxyethyl acrylate and benzyl acrylate. Examples of methacrylic acid esters include alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, octyl methacrylate, dodecyl methacrylate, stearyl methacrylate, and behenyl methacrylate, as well as aromatic ring-containing methacrylic acid esters such as phenoxyethyl methacrylate and benzyl methacrylate.

[0025] The hardness of the multilayer particles changes depending on the hardness of the second layer. For example, if the second layer is too soft, in addition to a decrease in damping, fusion and aggregation of the multilayer particles may occur, potentially reducing dispersibility. Therefore, it is desirable to adjust the Tg of the second layer to make the multilayer particles the desired hardness and to adjust the frequency range in which damping occurs. For example, the Tg of the second layer should be set to between -60°C and 40°C. The lower the Tg, the easier it is to exhibit damping in the higher frequency range (e.g., around 1000 to 10000 Hz). The Tg of the polymer forming the second layer can be measured by compressing the polymer to be measured into a sheet-like test piece and using a dynamic viscoelasticity measuring device.

[0026] (3) Structure, size, etc. Multilayer particles may include a first layer and a second layer (either a single layer or multiple layers), and may have, for example, a third layer between the first and second layers. If the outermost first layer is called the shell layer and the inner second layer is called the core layer, then the multilayer particles have a core-shell structure. From the viewpoint of good dispersibility in diene-based rubber and ease of achieving a dispersion form that yields the desired effect, it is desirable for the multilayer particles to be spherical.

[0027] The volume-average particle size of multilayer particles can be appropriately determined considering factors such as dispersibility and the durability of the vulcanized product. Suitable lower limits for volume-average particle size are 0.01 μm (10 nm), 0.04 μm (40 nm), and 0.08 μm (80 nm). Suitable upper limits for volume-average particle size are 1 μm (1000 nm), 0.8 μm (800 nm), 0.6 μm (600 nm), and 0.4 μm (400 nm). Dispersing nanometer-order multilayer particles in diene rubber can enhance durability. The volume-average particle size of multilayer particles can be measured, for example, using a particle size analyzer with latex in which the multilayer particles are dispersed in a solvent.

[0028] (4) Method for producing multilayer structured particles Multilayered particles can be produced using already known methods such as emulsion polymerization, suspension polymerization, and microsuspension polymerization. Among these, emulsion polymerization is preferable from the viewpoint of easily achieving uniform particle size. Emulsion polymerization can be carried out by adding water, monomers, polymerization initiators, emulsifiers, and, if necessary, chain transfer agents to a reaction vessel equipped with a stirrer and stirring. Furthermore, emulsion graft polymerization can produce multilayered particles in which the first layer is grafted to the second layer. In this case, first, a latex polymer of the second layer is produced by emulsion polymerization, and then the monomers of the first layer, polymerization initiators, etc. are sequentially added to this latex and polymerization is carried out.

[0029] [Other ingredients] The components of the vibration-damping rubber composition disclosed herein, other than the diene rubber and multilayer particles, are not particularly limited. Other suitable components for manufacturing vibration-damping rubber include vulcanizing agents, vulcanization accelerators, vulcanization aids, reinforcing agents, antioxidants, and plasticizers.

[0030] Examples of vulcanizing agents include sulfur (powdered sulfur, precipitated sulfur, insoluble sulfur) and organic sulfur compounds such as alkylphenol disulfide. Examples of vulcanization accelerators include guanidine-based, thiuram-based, thiazole-based, sulfenamide-based, and dithiocarbamate-based compounds. Examples of vulcanization aids include zinc oxide, stearic acid, palmitic acid, and magnesium oxide. Examples of reinforcing agents include carbon black and silica. Examples of anti-aging agents include carbamate-based, phenylenediamine-based, phenol-based, diphenylamine-based, quinoline-based, imidazole-based compounds, and waxes. Examples of plasticizers include process oils such as naphthenic oils, paraffinic oils, and aromatic oils.

[0031] [Method for producing vibration-damping rubber compositions] The vibration-damping rubber composition of this disclosure can be manufactured by kneading diene rubber, multilayer particles, and other components as needed using a kneader, Banbury mixer, open roll, twin-screw agitator, or other kneading equipment. For example, diene rubber, multilayer particles, and other components other than vulcanizing agents and vulcanization accelerators can be kneaded using a Banbury mixer or the like, and then vulcanizing agents and vulcanization accelerators can be added as appropriate, followed by further kneading using an open roll or the like.

[0032] The content of multilayer particles should be determined appropriately, taking into consideration the balance between the durability and damping properties of the vulcanized product. For example, from the viewpoint of improving damping properties, the content of multilayer particles should be 5 parts by mass or more per 100 parts by mass of diene rubber. 10 parts by mass or more, and even 15 parts by mass or more, is more preferable. On the other hand, from the viewpoint of suppressing the decrease in durability of diene rubber, the content of multilayer particles should be 50 parts by mass or less per 100 parts by mass of diene rubber. 40 parts by mass or less, and even 30 parts by mass or less, is more preferable.

[0033] In the vibration-damping rubber composition of this disclosure, one type of multilayer particle may be used, or two or more types of multilayer particles with different materials, thicknesses, structures, and volume-average particle diameters of the first and second layers may be used in combination. The diene rubber and multilayer particles used should be appropriately selected according to the application of the vulcanized product (vibration-damping rubber) so as to achieve the desired characteristics.

[0034] <Vibration-damping rubber> The vibration-damping rubber of this disclosure consists of a vulcanized product of the vibration-damping rubber composition of this disclosure. The vibration-damping rubber of this disclosure can be manufactured by holding the vibration-damping rubber composition of this disclosure at, for example, 150 to 170°C for 5 to 30 minutes to allow the vulcanization reaction to proceed. The vibration-damping rubber of this disclosure is suitable for applications requiring durability and damping properties, such as engine mounts, motor mounts, stabilizer bushings, and suspension bushings used in vehicles such as automobiles, as well as for vibration damping applications in the building and housing sectors. [Examples]

[0035] Next, the present disclosure will be described in more detail with reference to examples.

[0036] <Manufacturing of multilayered particles> [Multilayer structure particle A] (1) Formation of core particles (second layer) First, 3447g of deionized water, 40g of sodium carbonate (2.5% solids), and 20g of sodium lauryl sulfate (10% solids) were added to an 8L polymerization reactor, and the temperature was raised to 45°C while nitrogen was flowed through. Next, a solution of 0.011g of ferrous sulfate (FeSO4·7H2O) and 0.018g of ethylenediaminetetraacetate-disodium dissolved in 5.7g of deionized water, along with 16g of sodium formaldehyde sulfoxylate (5% solids), was added. Subsequently, a mixture of 1600g of butyl acrylate, 8g of allyl methacrylate, and 1g of t-butyl hydroperoxide (69% solids) was added over 240 minutes to carry out polymerization. During polymerization, sodium lauryl sulfate (10% solids) was added as needed. After the addition of sodium lauryl sulfate was completed, 0.35g of t-butyl hydroperoxide (69% solids) was added. Polymerization was terminated 30 minutes after the addition of t-butyl hydroperoxide to obtain core particles consisting of a crosslinked polymer. The Tg of the core particles was -50°C.

[0037] In this embodiment, the Tg values ​​of the first layer (shell layer) and the second layer (core particles) were measured by the following method. The polymer to be measured was compressed and molded into a sheet-like structure at 150°C for 10 minutes, and then 8 mm × 6 mm × 2 mm test pieces were cut out and used for measurement. A dynamic viscoelasticity analyzer (DVA-200, manufactured by IT Measurement Control Co., Ltd.) was used to measure Tg. The measurement conditions were as follows: frequency: 15 Hz, strain: 0.1%, heating rate: 4°C / min, temperature range: -50°C to 120°C, deformation mode: shear mode.

[0038] (2) Formation of the shell layer (first layer) A mixture of 400 g of allyl methacrylate and 0.7 g of t-butyl hydroperoxide (69% solids content) was added to the obtained core particles over 50 minutes. After the addition was complete, t-butyl hydroperoxide and sodium formaldehyde sulfoxylate were added as needed to achieve a conversion rate of 100%. In this way, core-shell structure graft copolymer latex A with a solids content of 33.5% was obtained. The obtained core-shell structure graft copolymer is referred to as multilayer structure particle A. The mass percentage of the shell layer in multilayer structure particle A was 20% by mass, and the Tg was 10°C. The volume-average particle diameter of multilayer structure particle A was 150 nm.

[0039] The volume-average particle diameter of the multilayer structure particles in this embodiment was measured using the obtained latex with the "NANOTRAC® WAVE" nanoparticle diameter measuring device manufactured by Microtrac.

[0040] [Multilayer structured particles B~D] Core-shell structure graft copolymer latexes B to D were obtained in the same manner as multilayer structure particle A, except that methyl methacrylate was added to the monomer constituting the core particles in the proportions shown in Table 1 below. The core-shell structure graft copolymers in each latex are referred to as multilayer structure particles B to D. The Tg of the core particles in multilayer structure particles B to D were -20°C, 10°C, and 30°C, respectively. The mass ratio of the shell layer, Tg, and volume-average particle diameter of multilayer structure particles B to D are the same as those of multilayer structure particle A. Note that multilayer structure particles A to D are included in the concept of porous structure particles in this disclosure.

[0041] [Multilayer structure particle E] (1) Formation of core particles (second layer) In a pressure vessel equipped with a stirrer, 29,000 g of deionized water, 0.395 g of disodium ethylenediaminetetraacetate, 0.237 g of ferrous sulfate (FeSO4·7H2O), and 16 g of sodium polyoxyethylene alkyl ether phosphate were charged. After deacidification, 20,000 g of butadiene, 200 g of sodium formaldehyde sulfoxylate (5% solids), and 11.5 g of paramentane hydroperoxide (52% solids) were added to initiate polymerization. During polymerization, sodium polyoxyethylene alkyl ether phosphate was added as needed, and the reaction was carried out at 50°C for 15 hours while maintaining the pH of the reaction solution at 6.5-7.5, until polymerization was completed with a conversion rate of 98% by weight. In this way, a diene-based rubber latex with a solids content of 40.0% was obtained. The Tg of the obtained diene-based rubber particles was -80°C, and the volume-average particle size was 130 nm.

[0042] (2) Formation of the shell layer (first layer) 3550g of the obtained diene-based rubber latex (40% solids) was placed in an 8L polymerizer, heated to 60°C, and nitrogen was flowed through it. A solution of 0.003g of ferrous sulfate (FeSO4·7H2O) and 0.005g of ethylenediaminetetraacetate-disodium dissolved in 1.6g of deionized water, along with 16g of sodium formaldehyde sulfoxylate (5% solids), was added. While maintaining the temperature at 60°C, a mixture of 440g of methyl methacrylate, 140g of styrene, and 2g of t-butyl hydroperoxide was added over 1 hour. After the addition was complete, t-butyl hydroperoxide and sodium formaldehyde sulfoxylate were added as needed to achieve a conversion rate of 100%. In this way, core-shell structure graft copolymer latex E with a solids concentration of 39.5% was obtained. The obtained core-shell structure graft copolymer is referred to as multilayer structure particle E. The shell layer mass percentage in multilayer particle E was 29% by mass, and the Tg was 104°C. The volume-average particle diameter of multilayer particle E was 150 nm.

[0043] [Multilayer structure particle F] Core-shell structured graft copolymer latex F was obtained in the same manner as for multilayer structured particle E, except that 17.4 g of allyl methacrylate was added during the formation of the shell layer. The obtained core-shell structured graft copolymer is referred to as multilayer structured particle F. The mass ratio of the shell layer, Tg, and volume-average particle diameter of multilayer structured particle F are the same as those of multilayer structured particle E.

[0044] Table 1 shows the constituent monomers, Tg, etc., of the first layer (shell layer) and second layer (core layer) in multilayer particles A to F. [Table 1]

[0045] <Manufacturing of rubber sheets> [Examples 1-7] Using the manufactured multilayer structured particles A to D as appropriate, a rubber sheet was manufactured as follows. First, natural rubber, multilayer structured particles, carbon black, zinc oxide, stearic acid, an antioxidant, and a plasticizer were kneaded together in a Banbury mixer at 120°C for 4 minutes. Next, a vulcanization accelerator and sulfur were added to this mixture and kneaded using an open roll to prepare an unvulcanized vibration-damping rubber composition. Then, the obtained vibration-damping rubber composition was press-molded at 150°C for 20 minutes to allow the vulcanization reaction to proceed, thereby producing a rubber sheet with a thickness of 2 mm. The manufactured rubber sheet is included in the concept of vibration-damping rubber of this disclosure.

[0046] The materials used and their proportions are shown in Table 2 below. Details of each material are as follows: Carbon black: "Seast (registered trademark) TA" manufactured by Tokai Carbon Co., Ltd. Zinc oxide: "Zinc Oxide Type 2" manufactured by Sakai Chemical Industry Co., Ltd. Stearic acid: "Beads Stearic Acid Sakura" manufactured by NOF Corporation. Anti-aging agent A: Amine-based anti-aging agent, "Ozonon® 6C" manufactured by Seiko Chemical Co., Ltd. Anti-aging agent B: Amine-based anti-aging agent, "Nonflex® RD" manufactured by Seiko Chemical Co., Ltd. Plasticizer: Naphthenic oil, "SUNTHENE® 410" manufactured by Nippon Sun Oil Co., Ltd. Vulcanization accelerator A: Thiazole-based vulcanization accelerator, "ACCEL(registered trademark) CZ" manufactured by Kawaguchi Chemical Industry Co., Ltd. Vulcanization accelerator B: Thiuram-based vulcanization accelerator, "ACCEL (registered trademark) TMT" manufactured by Kawaguchi Chemical Industry Co., Ltd. Sulfur: "Fine Sulfur Powder" manufactured by Karuizawa Smelting Co., Ltd.

[0047] [Comparative Examples 1-5] The rubber sheet was manufactured in the same manner as in the examples, except that multilayer particles were not used, or the type of multilayer particles was replaced with E or F.

[0048] <Evaluation of rubber sheets> [Evaluation Method] (1)Durability From the manufactured rubber sheet, a dumbbell-shaped sample of type 3, as specified in JIS K6251:2023, was cut out, and a stretch fatigue test was performed using this sample. The stretch fatigue test was conducted in accordance with the bending crack initiation test specified in JIS K6260:2017. The number of stretches at which the sample broke (number of stretches to break) was measured, and the measured number of stretches to break was compared with a comparative example with the same rubber composition as a baseline. Table 2 below shows the number of stretches to break for each example sample as a ratio (number of stretches for example / number of stretches for comparative example) with the number of stretches to break of the comparative example sample set to 1.0.

[0049] (2) Damping Dynamic property tests were conducted using the manufactured rubber sheets in accordance with JIS K6385:2012, and the damping properties were evaluated based on the value of the loss coefficient (tanδ). In the dynamic property tests, a dynamic viscoelasticity measuring device was used to measure tanδ at a frequency of 15 Hz and at temperatures in 10°C increments from -20°C to 20°C. The measured tanδ values ​​were compared with comparative examples that had the same rubber composition as a reference. Table 2 below shows the tanδ values ​​of the samples from each example as the difference between the tanδ of the reference comparative example sample and the tanδ of the comparative example sample (tanδ of the example - tanδ of the comparative example). For comparative examples 3 to 5, tanδ was measured only at 20°C.

[0050] [Evaluation Results] Table 2 summarizes the components and evaluation results for each sample. In Table 2, under "Form number due to differences in rubber components," differences in the amount of carbon black are indicated as circle 1, circle 2, and circle 3, while differences in the amounts of plasticizer, vulcanization accelerator, and sulfur are indicated as -1 and -2. [Table 2]

[0051] As shown in Table 2, the samples from Examples 1 to 7, which used any of the multilayer particle A to D, showed improved damping with increased tanδ above 0°C while maintaining durability, compared to the comparative example samples that did not use multilayer particle. In particular, the samples from Examples 1, 3, and 4, which used multilayer particle A and B with low core layer Tg, showed increased tanδ and improved damping even below 0°C. That is, the samples from Examples 1, 3, and 4 demonstrated high performance in reducing high-frequency vibrations. In contrast, the sample from Comparative Example 4, which used multilayer particle D, in which the shell layer was formed without using a monomer (allyl methacrylate) having a vulcanization-reactive functional group, and the core layer was also formed without using an acrylic acid ester, showed a significant decrease in durability. Furthermore, the sample from Comparative Example 5, which used multilayer particle E, in which the core layer was formed without using an acrylic acid ester and the core layer Tg was -80°C, showed relatively good durability, but the improvement in damping was small. [Industrial applicability]

[0052] The vibration-damping rubber disclosed herein is suitable for applications requiring durability and damping properties, such as engine mounts, motor mounts, stabilizer bushings, and suspension bushings used in vehicles such as automobiles, as well as for vibration-damping applications in the building and housing sectors.

Claims

1. Diene-based rubber and A multilayer particle having a first layer forming the outermost layer of the particle, and a second layer positioned inside the first layer, It has, The first layer consists of a polymer formed by polymerizing vinyl monomers containing monomers having vulcanization-reactive functional groups. The second layer is a single or multiple layer, and is characterized by being a polymer formed by the polymerization of one or more monomers containing an acrylic acid ester, making it a vibration-damping rubber composition.

2. The vibration-damping rubber composition according to claim 1, wherein in the first layer, the monomer having the vulcanization-reactive functional group is one or more selected from allyl methacrylate, diallyl phthalate, triallyl isocyanurate, 1,2-butadiene, and 1,3-butadiene.

3. The vibration-damping rubber composition according to claim 1, wherein the polymer forming the second layer is crosslinked.

4. The vibration-damping rubber composition according to claim 1, wherein the glass transition temperature of the second layer is -60°C or higher and 40°C or lower.

5. The vibration-damping rubber composition according to claim 1, wherein the mass ratio of the first layer in the multilayer structured particles is 5% by mass or more and 50% by mass or less when the total amount of the multilayer structured particles is 100% by mass.

6. The vibration-damping rubber composition according to claim 1, wherein the content of the multilayer structured particles is 5 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the diene rubber.

7. A vibration-damping rubber comprising a vulcanized product of the vibration-damping rubber composition described in claim 1.

Citation Information

Patent Citations

  • Rubber vibration insulator

    JP2006143860A

  • Vibration-proof rubber composition and vibration-proof rubber member

    JP2019131761A

  • Rubber composition for tires, tire and molded body

    WO2020067414A1